2021
DOI: 10.26554/ijems.2021.5.1.5-12
|View full text |Cite
|
Sign up to set email alerts
|

Thematic Evolution of Municipal Solid Waste Management Research

Abstract: This study aims to learn the thematic evolution of Municipal Solid Waste Management research by revising Scopus indexed publications between 2001 and 2020. Within a longitudinal system, a scientific co-word inspection is conducted from 2001 to 2020. The publication series was split into two periods; the first period is from 2001 to 2010, and the second period is from 2011 to 2020. The findings, impact rates, and Municipal Solid Waste Management research’s conceptual growth are verified. In this emerging field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…This trend suggests a growing interest in solid waste management research during this period. This study agrees with the bibliometric studies conducted by Abdullah et al (2021) and Fu et al (2010); they concluded that a rise in publications during this period indicated that the proper disposal of solid waste had emerged as a significant environmental issue worldwide.…”
Section: Publication Growth Trendssupporting
confidence: 91%
See 2 more Smart Citations
“…This trend suggests a growing interest in solid waste management research during this period. This study agrees with the bibliometric studies conducted by Abdullah et al (2021) and Fu et al (2010); they concluded that a rise in publications during this period indicated that the proper disposal of solid waste had emerged as a significant environmental issue worldwide.…”
Section: Publication Growth Trendssupporting
confidence: 91%
“…Improper disposal of solid waste can result in pollution of the air, water, and soil, leading to negative impacts on human health and the environment (Ifeoluwa, 2019;Massoud et al, 2023;Mekonnen et al, 2020). Consequently, studying solid waste management practices enables informed decisions that promote ecosystem health and productivity, ensuring the sustainability of our planet's resources (Abdullah et al, 2021). The importance of efficient solid waste management in preserving public health, preserving resources, mitigating climate change, and safeguarding the environment is undoubtedly evident.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These volumes had a significant impact on the ecosystem, endangering the globe and posing a threat to natural resources. Uncollected waste and improperly disposed waste have a substantial impact on public health and the environment (Abdullah et al, 2021;Kaza et al, 2018). Furthermore, it also results in a long-term economic impact on environmental recovery, which frequently leads to increased costs of developing and operating basic, appropriate waste management systems (Kaza et al, 2018;Sreenivasan et al, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The bibliometric evaluation includes identifying the author's research areas, the citation network, and the authors' keywords Kar & Wray, 2016;Sofyan, 2022). Moreover, bibliometric data can be utilised to analyse any credible form of knowledge for a given bibliometric study (Abdullah, 2021) Bibliometric analysis can be used to examine bibliometric data gathered from various databases, such as Scopus, Web of Science, Google Scholar, Microsoft Academics, or Dimensions (Abdullah et al, 2021). In addition, the analysis can be visualised using multiple tools, including VOSviewer, SciMAT, and ScientoPy .…”
Section: Bibliometric Analysismentioning
confidence: 99%